Programming with MATLAB for scientists : a beginner's introduction - Mikhailov, Eugeniy E., 1975- (CRC Press, 2017)
"This book offers an introduction to the basics of MATLAB programming to scientists and engineers. The author leads with engaging examples to build a working knowledge, specifically geared to those with science and engineering backgrounds. The reader is empowered to model and simulate real systems, as well as present and analyze everyday data sets. In order to achieve those goals, the contents bypass excessive "under the hood" details, and instead gets right down to the essential, practical foundations for successful programming and modeling. Readers will benefit from the following features:Teaches programming to scientists and engineers using a problem-based approach, leading with illustrative and interesting examples.Emphasizes a hands-on approach, with "must know" information and minimal technical details.Utilizes examples from science and engineering to showcase the application of learned concepts on real problems.Showcases modeling of real systems, gradually advancing from simpler to more challenging problems.Highlights the practical uses of data processing and analysis in everyday life."- Resumé vydavatel
Keywords: MATLAB (software); počítačové programy; numerická analýza; zpracování dat; computer programs; numerical analysis; data processing; příručky; elektronické knihy; handbooks and manuals; electronic books